The Impact of Hormonal Therapy on Autologous Microvascular Breast Reconstruction: A Systematic Review and Meta-analysis - Miroslava Verbat, BS; Gauthier Zinner, MS; Edward T.C. Dong; Carlo M. Oranges, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Hormonal therapy (HT) is pivotal in managing hormone receptor–positive breast cancer. However, in autologous microvascular breast reconstructions (AMBRs), HT raises concerns, particularly regarding venous thromboembolic (VTE) risk and its potential impact on flap viability. This systematic review and meta-analysis aimed to evaluate the impact of HT on complications of AMBR. Methods:. We performed a systematic review and meta-analysis of all comparative studies reporting postoperative complications of AMBR in patients receiving HT in comparison with a control group. All types of free flaps were included. Complications were categorized and compared. Odds ratios and 95% confidence intervals were calculated using a random-effects model. Results:. Eight studies, encompassing 4776 flaps performed on 3796 patients undergoing AMBR with or without HT, were included. Patients undergoing HT were treated with either selective estrogen receptor modulators (SERMs) or aromatase inhibitors. Five studies compared both treatments to a control group, whereas 3 studies focused on tamoxifen. Only studies with retrospective design could be included. There was no statistically significant difference between the 2 groups in terms of overall flap complication rates, partial and total flap loss, flap fat necrosis, flap pedicle arterial and/or venous thrombosis, or systemic VTE. Subgroup analysis revealed a significantly higher risk of systemic VTE in the SERMs group compared with controls, while other complications were not significant. Conclusions:. Our results show that HT does not increase the risk of flap complications in the context of AMBR, whereas SERMs increase the risk of systemic VTE. Further research with prospective studies is warranted to confirm these findings.